Defatted Kenaf (Hibiscus cannabinus L.) Seed Meal and Its Phenolic-Saponin-Rich Extract Protect Hypercholesterolemic Rats against Oxidative Stress and Systemic Inflammation via Transcriptional Modulation of Hepatic Antioxidant Genes. (22nd April 2018) - Chan, Kim Wei; Ismail, Maznah; Mohd Esa, Norhaizan; Mohamed Alitheen, Noorjahan Banu; Imam, Mustapha Umar; Ooi, Der Jiun; Khong, Nicholas M. H.
Abstract : The present study aimed to investigate the antioxidant and anti-inflammatory properties of defatted kenaf seed meal (DKSM) and its phenolic-saponin-rich extract (PSRE) in hypercholesterolemic rats. Hypercholesterolemia was induced using atherogenic diet feeding, and dietary interventions were conducted by incorporating DKSM (15% and 30%) or PSRE (at 2.3% and 4.6%, resp., equivalent to the total content of DKSM-phenolics and saponins in the DKSM groups) into the atherogenic diets. After ten weeks of intervention, serum total antioxidant capacities of hypercholesterolemic rats were significantly enhanced by DKSM and PSRE supplementation (p < 0.05 ). Similarly, DKSM and PSRE supplementation upregulated the hepatic mRNA expression of antioxidant genes (Nrf2, Sod1, Sod2, Gsr, and Gpx1) of hypercholesterolemic rats (p < 0.05 ), except for Gpx1 in the DKSM groups. The levels of circulating oxidized LDL and proinflammatory biomarkers were also markedly suppressed by DKSM and PSRE supplementation (p < 0.05 ). In aggregate, DKSM and PSRE attenuated the hypercholesterolemia-associated oxidative stress and systemic inflammation in rats, potentially by enhancement of hepatic endogenous antioxidant defense via activation of the Nrf2-ARE pathway, which may be contributed by the rich content of phenolics and saponins in DKSM and PSRE. Hence, DKSM and PSRE are prospective functional food ingredients for the potential mitigation of atherogenic risks in hypercholesterolemic individuals.